Developing a framework on success performance of community-based homestay tourism programme: evidence from insider of homestay / Nor Syuhada Zulkefli, Roslizawati Che Aziz and Aifa Rozaini Mohd Radzol - Zulkefli, Nor Syuhada; Che Aziz, Roslizawati; Mohd Radzol, Aifa Rozaini (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Through the domain of Communities-Based Tourism (CBT) in tourism sector, the Malaysia Homestay Program (MHP) was introduced to the community with a purpose to enhance the local communities' livelihood and economic sustainability. In the context of the sustainable development goals (SDGs) 2030, CBT has been used as an approach to achieve progress on SDG1-No Poverty and SDG11-Sustainable Cities and Communities. However, the homestay operators facing a great challenge to sustain their businesses and among the reasons are village landscape, inefficient networking, lack of cooperation and commitment from homestay operators, exploitation of external parties, as well as ineffective promotional and marketing activities. To overcome these challenges, this study would like to understand what make one homestay operator success with their business. Therefore, this study investigates the successful performance factors of community based in MPH. The data was collected using a qualitative approach where 17 key informants were interviewed, and the data was interpreted using a Nvivo 12 software. Twelve criterion of success factors of MPH were identified and seven very important dimensions to attract more visitors are revealed. The findings also highlighted the three new dimensions (i.e; recognition and previous awards, entrepreneurship, and uniqueness of product and package design) for homestay operators to attract more visitors, to grow and sustain business for their livelihood and economic prosperous. These dimensions would be designed for the future homestay business to be successful for a whole-of-community.